Divergent innervation of the olfactory bulb by distinct raphe nuclei - Steinfeld, Raphael; Herb, Jan Thomas; Sprengel, Rolf; Schaefer, Andreas T.; Fukunaga, Izumi (The journal of comparative neurology, 2015)
The raphe nuclei provide serotonergic innervation widely in the brain, thought to mediate a variety of neuromodulatory effects. The mammalian olfactory bulb (OB) is a prominent recipient of serotonergic fibers, particularly in the glomerular layer (GL), where they are thought to gate incoming signals from the olfactory nerve. The dorsal raphe nucleus (DRN) and the median raphe nucleus (MRN) are known to densely innervate the OB. The majority of such projections are thought to terminate in the GL, but this has not been explicitly tested. We sought to investigate this using recombinant adeno-associated viruses (rAAV)-mediated expression of green fluorescent protein (GFP)-synaptophysin targeted specifically to neurons of the DRN or the MRN. With DRN injections, labeled fibers were found mostly in the granule cell layer (GCL), not the GL. Conversely, dense labeling in the GL was observed with MRN injections, suggesting that the source of GL innervation is the MRN, not the DRN, as previously thought. The two raphe nuclei thus give dual innervation within the OB, with distinct innervation patterns. J. Comp. Neurol. 523:805-813, 2015. © 2015 The Authors The Journal of Comparative Neurology Published by Wiley Periodicals, Inc.
Gesehen am 22.06.2020